Increasing Community Economic Capability Through Optimizing Urban Farming Areas - Citra Sarasmitha; Erik Irmansyah; Rayhan Ananta Firmansyah; Zulaika; Shekinah Beatrice Agatha; Erina Kusuma Ningrum (PT FORMOSA CENDEKIA GLOBAL, 2023)
This service program aims to optimize the urban farming area in Genitri Village, Pisang Candi Subdistrict, Malang City so that it can produce processed agricultural products with high marketability. Partners have problems regarding the unavailability of facilities and infrastructure to support urban farming activities. The service team was also present in the work program, including adding varieties of vegetable and fruit plants, building irrigation and sanitation channels, building public bathrooms, making processed agricultural products, and marketing products. The results of the service show that optimizing facilities and infrastructure can help make it easier for residents to cultivate urban farming areas to produce processed products with high selling value. The profits obtained from selling processed agricultural products are proven to provide high profits so that they can improve the economy of residents as MSMEs